WHY PROFITABILITY NEGATIVELY AFFECT THE CAPITAL STRUCTURE IN FOOD AND BEVERAGE INDUSTRY? - Sukirman, Oman (Universitas Pendidikan Indonesia, 2019)
The capital structure became the foundation for a company. Conditions of the capital structure will greatly affect the survival of a company. The financial manager is obliged to maintain the stability and the good condition of the capital structure with capital sourced from the selection of internal and external. The company's profit is the source of internal capital, so that profitability has a relationship with the capital structure. The purpose of this study was to obtain evidence on whether profitability has a negative impact on the capital structure. This study used secondary data from company financial statements of Consumer Goods Industry sector, more specifically Food and Beverage sub-sector obtained from the Indonesian Stock Exchange (BEI). The sample used was 14 companies of the food and beverage industry. The analysis technique used was a simple linear regression. The results showed that there was a negative effect on the profitability of the capital structure, which means that food and beverage companies have formed a theory of Pecking Order in which internal financing has used retained earnings.